Color tissue doppler imaging of tricuspid annular plane systolic and diastolic excursion in children: A comparison of normal, volume‐overloaded and pressure overloaded right ventricles. Issue 3 (20th February 2022) - Malakan Rad, Elaheh; Amani, Sude; Ilali, Hamidreza Mirzaei; Sedaghat, Abdullah; Zanjani, Keyhan Sayadpour; Moghadam, Ehsan Aghaei; Shabanian, Reza; Zeinaloo, Ali Akbar
Abstract: Background: Tricuspid annular plane (TAP) systolic excursion (TAPSE) is a reproducible M‐mode parameter for the measurement of longitudinal shortening of the right ventricle (RV). To date, all attention has been focused on the systolic excursion of TAP and the diastolic excursion of the annular plane back to the base has been ignored. This study aims to compare the quantitative (excursion, slope, and duration) and qualitative (velocity, acceleration, and indentation) characteristics of TAP systolic and diastolic excursion, using color tissue Doppler imaging, in three groups of children with normal RV (NORV), volume overloaded RV (VORV), and pressure overloaded RV (PORV) and normal pulmonary arterial pressure. Subjects and methods: A prospective case‐control study was performed in three groups of children with normal heart, VORV and PORV. TAPSE and tricuspid annular plane diastolic excursion (TAPDE) were quantitatively and qualitatively analyzed and compared between the three groups. Statistical analysis was performed using IBM SPSS Statistics for Windows. Results: TAPSE, TAPDE, TAPSE slope, TAPSE slope/TAPDE slope, TAPDE duration and TAPDE duration/RR interval were lower in PORV (TAPSE: PORV: 14.45 ± 4.30, NORV: 20.45 ± 5.46, P  = .003, TAPDE:PORV: 14.39 ± 4.61, NORV: 20.28 ± 5.65, P  = .004, TAPSE slope:PORV: 4.79 ± 1.40, NORV: 7.15 ± 1.98, P  = .001, .001, TAPDE duration:PORV: 201.1 ± 87.9 ms, NORV: 292.1 ± 97.9, P  = .006, TAPDE duration/RR interval: PORV: .37 ± .09, NORV: .48 ± .08, P  = .0002). Conclusion: Pressure‐overload on RV produced more impairment of TAPSE and TAPDE patterns than volume overload. Values of TAPSE and TAPDE in patients with VORV and PORV stay in two ends of the normal spectrum. The harmful impact of pre‐tricuspid volume overload seems to be less than the post‐tricuspid volume overload.